PENINGKATAN HASIL BELAJAR SISWA MELALUI MEDIA GAMBAR DALAM PEMBELAJARAN IPA MATERI SIKLUS MAKHLUK HIDUP DI KELAS IV SDN 03 SUNGAI RUMBAI TAHUN PELAJARAN 2021/2022 - Suwardi (STKIP Subang, 2022)
This research originated from the common understanding of students towards science learning in elementary schools. This research is due to the inadequate facilities for this learning media. The use of the method is carried out with educators who are monotonous as long as students do not participate in learning. Visual media can teach students about natural resources that have yet to be studied in the surrounding environment. This research was conducted to describe the level of mastery of student material and the shortcomings and advantages of the methods used by teachers in the learning process to motivate and train students' independence in completing science learning. This study used classroom action research with two cycles. Each cycle consists of design, observation, implementation, reflection, and revision. Analysis data obtained from formative test results, observation sheets of learning activities. The results showed that student learning outcomes increased based on cycle I and cycle II, with the limit of completeness of grades in cycle I to 60% and increased in cycle II to 85%. The results of this increase have proven effective in terms of the use of illustrated media in science learning in grade IV SDN 03 Sungai Rumbai. They can be used as one of the considerations and alternatives in science learning.